The Effects of Information-Motivation-Behavioral Skills Program on Knowledge, Attitude, and Behavioral Skills toward Pregnancy Prevention and Sexually Transmitted Infections among Female Junior High School Students - Maneesri, Suchanaree; Tipwareerom, Worawan; Juntarawijit, Yuwayong (NU Journal of Nursing and Health Sciences, 2023)
The purposes of this Quasi-experimental research were to examine the effects of an Information-Motivation-Behavioral Skills on knowledge, attitude, behavioral skills toward pregnancy prevention and sexually transmitted infections among female junior high school. The sample consisted of female in high school of age 12 – 13 years old. The sample included 70 participants. There are thirty-five experimental groups and thirty-five control groups. The experimental group received the Information-Motivation-Behavioral Skills program by application of the IMB model. The control group received the normal curriculum. The duration of this program was 8 weeks. Research instruments were questionnaires consisting of three parts: 1) Knowledge on the prevention of pregnancy and sexually transmitted infections, tested using the KR-20, which showed a result of 0.74. 2) Attitude on the prevention of pregnancy and sexual transmitted infections, with reliability determined by a Cronbach’s alpha coefficient of 0.74, and 3) Behavioral skills on the prevention of pregnancy and sexual transmitted infections, with reliability determined by a Cronbach’s alpha coefficient of 0.74. Data was analyzed using descriptive statistics, including independent sample t-test and paired t-test. The results indicated the following: The experimental group had higher mean scores of knowledge, attitude and behavioral skills of pregnancy prevention and sexual transmitted infections than before joining the program (p<0.001), The experimental group had higher mean scores of knowledges on the prevention of pregnancy and sexually transmitted infections than the control group (p<0.05) and The experimental group had higher mean scores of Attitudes and Behavioral skills on the prevention of pregnancy and sexually transmitted infections than of the control group (p< .001). The results of this study suggest that health personal can use the results of this study to plan for the prevention of adolescent pregnancy and sexually transmitted infections. There is an online teaching method for transmitting health information. To provide students with accurate and continuous access to gender information.